2020
DOI: 10.3390/su12114368
|View full text |Cite
|
Sign up to set email alerts
|

Application of Circular Economy Techniques for Design and Development of Products through Collaborative Project-Based Learning for Industrial Engineer Teaching

Abstract: Collaborative project-based learning aims to get students to take responsibility for their knowledge processes. The objective of this research is to analyze the viability of applying circular economy techniques for the design and development of products, through learning based on collaborative projects in industrial engineering. A survey was carried out between 2015 and 2019 on final year students of industrial engineering in Spain, from five different academic years. The responses obtained were analyzed stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 47 publications
(94 reference statements)
2
17
1
Order By: Relevance
“…In order to corroborate that these items can constitute independent constructs, Cronbach’s alpha coefficients were calculated for each of these constructs, and the following values were obtained: 0.765 (C1) and 0.862 (C2): both values higher than 0.7. Hence, these can be considered as independent constructs [ 7 , 9 , 39 , 48 ]. These results are of interest because the factors are grouped and therefore allow us to look for relationships with other variables and to establish strategies to influence these variables.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to corroborate that these items can constitute independent constructs, Cronbach’s alpha coefficients were calculated for each of these constructs, and the following values were obtained: 0.765 (C1) and 0.862 (C2): both values higher than 0.7. Hence, these can be considered as independent constructs [ 7 , 9 , 39 , 48 ]. These results are of interest because the factors are grouped and therefore allow us to look for relationships with other variables and to establish strategies to influence these variables.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve these goals, the participation of all actors is required, including governments, civil society, enterprises, and non-governmental organisations [ 4 , 5 , 6 ]. The 2030 Agenda must be understood in a joint way, since the SDGs are interconnected with each other [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [9], the authors take a look at how the circular characteristics of the economy affect the future of industrial engineers. It is demonstrated that the industrial engineer of the future is one to master concepts of circular economy strategies.…”
Section: Industrial Engineering Trendsmentioning
confidence: 99%
“…The SDGs are closely related to each other [5,49]. The achievement of one has consequences on others, this may be the case of education [49] which, apart from being related to SDG 4, is also related to others such as SDG 5 (Gender Equality) or SDG 12 (Sustainable Consumption and Production), etc. Something similar occurs with the construction and implementation of CS [48].…”
Section: Relationship Sdg-sustainabilitymentioning
confidence: 99%